2018
DOI: 10.1371/journal.pone.0204890
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Motivational Interviewing on adult behaviour change in health and social care settings: A systematic review of reviews

Abstract: BackgroundThe challenge of addressing unhealthy lifestyle choice is of global concern. Motivational Interviewing has been widely implemented to help people change their behaviour, but it is unclear for whom it is most beneficial. This overview aims to appraise and synthesise the review evidence for the effectiveness of Motivational Interviewing on health behaviour of adults in health and social care settings.MethodsA systematic review of reviews. Methods were pre-specified and documented in a protocol (PROSPER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
166
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(180 citation statements)
references
References 132 publications
2
166
0
12
Order By: Relevance
“…This is highlighted in a recent systematic review by Frost et al . , which explored reviews of motivational interviewing on health behaviour in adults. This included 30 reviews, seven of which specifically focused on the management of diabetes.…”
Section: Management Of Distress: Individual Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is highlighted in a recent systematic review by Frost et al . , which explored reviews of motivational interviewing on health behaviour in adults. This included 30 reviews, seven of which specifically focused on the management of diabetes.…”
Section: Management Of Distress: Individual Interactionsmentioning
confidence: 99%
“…There are limited data measuring observed communication behaviours between patient and providers in the consultation and its impact on diabetes distress [19,20]. This is an important consideration as perceived skill use and actual delivery can vary considerably, contributing to variations seen in clinical outcomes [49]. This is highlighted in a recent systematic review by Frost et al [49], which explored reviews of motivational interviewing on health behaviour in adults.…”
Section: Management Of Distress: Individual Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…One practice employed by the Wholesome Wave FVRx program to make lasting changes in participants' shopping habits is motivational interviewing. This invokes patients to change unhealthy behaviors and has proven effective with patients with diabetes 35,36,37,38 . The combination of education, motivational interviewing, and fruit and vegetable vouchers address the barriers to improving participants' diets and engages them to make lasting changes 39,40,41,42 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant evidence supporting the effectiveness of MI, less has been written about effective ways to teach clinicians and trainees to reliably perform high-quality motivational interviewing in the general hospital setting [14][15][16]. This is problematic not only because studies have demonstrated a link between MI and patient-level changes in behavior but also because these changes are mediated by the quality of the technique itself and the quality of empathy exhibited by the therapist [17].…”
mentioning
confidence: 99%